Closing the Gap in the Municipal Solid Waste Management Between Metropolitan and Regional Cities from Developing Countries: A Life Cycle Assessment Approach - Vasquez-Perez, O; Espinoza-Perez, A (Elsevier Ltd, 2021)
Municipal solid waste (MSW) management is an important challenge in developing and emerging countries, where two realities co-exist. On the one hand, their metropolitan cities exhibit an integrated MSW system with a specialized fleet for the collection and landfills for the final disposal, concentrating on environmental initiatives such as municipal recycling programs. On the other hand, their regional cities show an MSW system based on adapted transports for collection and open dumps for final disposal. Besides, they face other environmental problems due to local conditions. This research proposes a life cycle assessment (LCA) approach to close the gap between these two realities. In particular, we study the city of Valdivia (Chile), one of the main regional capitals of South America, which shares similarities with other southern regional cities in the Global South. This city disposes 95% of its MSW in open dumps and presents one of the highest environmental pollution rates in Latin America. We analyze the greenhouse gas (GHG) emissions and energy performance of six scenarios, seeking a solution for these problems. The results obtained show that a waste-to-energy scenario would generate savings of GHG emission and particulate matter, reaching 11.3% and 21.8%, respectively. Using our LCA approach, we can provide environmental evidence to highlight the importance of improving MSW management in regional cities, closing the gap with MSW management in metropolitan cities, and contributing to national targets such as United Nations Sustainable Development Goals and Nationally-Determined Contributions. © 2021 Elsevier Ltd